THE CONCEPT OF SCIENTIFIC THINKING FROM AN ISLAMIC POINT OF VIEW: FUSION WITH A WESTERN PERSPECTIVE - Winarti Winarti; Nasrullah Nasrullah; Muzhir Rinaldi; Darwin Effendi (Universitas PGRI Palembang, 2023)
Indonesia is currently in the midst of Industrial Revolution 4.0. This indicates that the development of the Internet, the latest technologies, artificial intelligence and nanotechnology should be initiated by people of high character and harmony within society. People are constantly growing and always adapting to existing changes. To cope with this, we humans, as creators or users of revolutions, are expected to support scientific thinking activities. The process of computation and dies. Analysis of data or information. Statistics is the process analysis and verification of data or information, which ultimately indicates the validity of the data or information. From an Islamic point of view, humans serve Allah SWT and were created as caliphs or leaders of the smallest (family, school, largest (ministry or government)) realms. In essence, human beings were implicitly created by an Almighty Creator to cooperate and live in societies, nations and families. However, to achieve this goal we need the ability to think scientifically, and this was made clear to his Apostle in the Koran and Sunnah. continue to understand without interruption. Contextual analysis techniques related to the Islamic perspective as well as the concept of scientific thinking in the Islamic perspective. From this we can gain some insight. In other words, in order to be able to carry out scientific thinking activities thoroughly, we need three functions, which are the key pillars of scientific thinking (language, mathematics, statistics) and conceptual logic related to Al-Quran and Hadith.